Pengaruh Media Pembelajaran Pop-Up Book Terhadap Minat Belajar Siswa Pada Mata Pelajaran IPA - Khaidir Fadil; Ratnasih Apriliani; Rusdi Kasman (Jurnal Evaluasi dan Pembelajaran, 2023)
The purpose of this study was to find out how interested fifth-grade students were in learning about science and to see if the use of Pop-Up Books as a learning tool had a big effect on students' interest in learning about science in class V. This study used a quasi-experimental design with a None-equivalent Control Group Design and a sampling method called "purposive sampling." This study looked at 75 fifth-grade students from SDN Batu 3 Bogor, which were divided into two class groups, namely class VB as the experimental group who took part in learning using Pop Up Book media and class VA as the control group who took part in learning using ordinary learning media. Data collection techniques using questionnaires. The questionnaire used by researchers according to its type is a closed questionnaire, which is a questionnaire that provides various alternative answers, and the respondent only needs to choose the appropriate answer. The form of the questionnaire in this study was 26 choices using 4 alternative answers, namely, strongly agree (SS), agree (S), disagree (TS), and strongly disagree (STS). The data analysis technique used in this study used the t-test with the help of the SPSS version 23.0 computer. The results of the study show that, based on the data from the previous research, there is a link between the use of Pop Up Book learning media and students' interest in learning about science. The results of research on students' learning interests. Following are the average scores of the two classes. From the two classes, it is explained that the average post-test score is 59.2. Meanwhile, the control class got an average posttest score of 47.0 with a difference in the value of 12.1.